1970
DOI: 10.1007/bf00356236
|View full text |Cite
|
Sign up to set email alerts
|

The influence of extractives on the radiation stability of wood

Abstract: The critical dose above which a decrease in toughness of Western Red Cedar and Peroba wood, extracted with benzene-alcohol is noted, was determined to be approximately 0.5 • 106 rad lower than that for the same non-extracted species. Investigations have shown that the presence of benzene-Mcohol extractives in wood raises its radiation stability. This conclusion is supported by the fact that the toughness curve which generally falls with increasing doses of absorbed irradiation shows a steeper decrease for extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1979
1979
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Toughness is increased by extracting extraneous compounds with an alcohol-benzene mixture (Raczkowski 1968, Lawniczak andRaczkowski 1970).…”
Section: Forest Products Laboratory 1955)mentioning
confidence: 99%
“…Toughness is increased by extracting extraneous compounds with an alcohol-benzene mixture (Raczkowski 1968, Lawniczak andRaczkowski 1970).…”
Section: Forest Products Laboratory 1955)mentioning
confidence: 99%
“…The densification caused by the latter treatment is accompanied by some flow of lignin. (46,52,58,59,78) Because high energy radiation increases the dimensional stability of wood, it is to be expected that doses of gamma or beta radiation controlled to below the degradation limit would modify the hydrophylic properties of the radiation-sensitive hemic elluloses and celluloses. The presence of water and oxygen increases the complexity of all possible reactions.…”
Section: Physical Treatmentmentioning
confidence: 99%
“…Nevertheless, the influence of radiation on wood extractives has not been clarified in detail. Lawniczak and Raczkowski [ 12 ] concluded that the extractive prevents the wood for mechanical property losses caused by a radiation process.…”
Section: Introductionmentioning
confidence: 99%